Influence of Allulose on the Physicochemical and Sensory Attributes of Papaya Jam - Ammanullah, Muhammad Azri; Mohamad Fuzi, Siti Fatimah Zaharah (Enhanced Knowledge in Sciences and Technology, 2025)
Excessive consumption of refined sugar widely used for its sweetening and preserving properties, poses significant health risks, leading to a global shift toward healthier alternatives like natural sweeteners. Transforming papaya into jam effectively reduces postharvest losses by extending the shelf life of papaya highly perishable fruit. This study objective is to replace normal sugar with allulose and conduct physicochemical and sensory analyses. Ripe papayas were selected, washed, peeled, and treated to inhibit papain activity using methods such as steaming, steaming with vinegar, steaming with vitamin C, and steaming with Sunquick. Allulose was added to the papaya pulp, and citric acid was used to adjust the pH before storing the jam in jars. The chosen method was applied to the jam production process again with different concentrations of allulose (150 g, 190 g, 225 g, 300 g). Among the tested methods, steaming was the most effective method to eliminate unwanted odours produce by papain while preserving natural flavours and nutritional value of papaya. Detailed analyses evaluated total dissolved solids (Brix), pH, moisture content, viscosity, and sensory attributes like colour, odour, texture, taste, and overall acceptance. The 190 g sample achieved the highest overall acceptance score of 6.520, attributed to its balanced sweetness (Brix value of 67.10) and optimal viscosity (12,587.00). In contrast, the 300 g sample, with a Brix value of 74.80 and high viscosity (26,426.70), was less preferred due to excessive sweetness and thickness. Sensory evaluation showed the 190 g sample scored highest for overall acceptance (6.520), colour (7.540), texture (7.020) and taste (6.620). These findings highlight the importance of optimizing allulose levels to balance physicochemical properties and sensory appeal, creating a sustainable, nutritious, and consumer-friendly product.